MODEL DEVELOPMENT OF SUCCESSION PLANNING IN SUBSIDIARY COMPANIES ENGAGED IN THE INSURANCE INDUSTRY - Primadi Candra Susanto; Naik Henokh Parmenas (ABNUS Publisher, 2021)
In this study using the Qualitative Phenomenology Method, the purpose of this study is to provide input regarding the proper retention plan formulation procedures and provide input regarding the procedures for identifying talent readiness to meet the needs of a critical position. Based on the analysis of the application of succession planning in insurance companies, it can be concluded that the following matters The implementation of succession planning at the subsidiary company has not been carried out optimally because it is still at the create development plans stage or the 4th stage of the seven stages of the succession planning process, the company is mature enough Identified talent and talent mapping for 15 manager candidates to obtain 2 candidates in the Ready Now category, 8 candidates in the Ready With Development category and five candidates in the Not Ready Yet category. For the candidates mentioned above, the Company has also compiled a talent development strategy (talent development strategy), which includes a number of development programs, including in-house training, coaching and mentoring, as well as special assignments. The development program is adjusted to the proficiency level of each candidate, based on the results of the assessment that has been carried out. right by the Company. The output of the development program carried out is a number of talent readiness to fill critical positions in the Company. Based on the analysis that has been done, the talent readiness of the subsidiary company ranges from 1-2 years. To maintain the talents the Company already has, the Company has also prepared a retention planning strategy. The retention strategy undertaken by the Company is more aimed at increasing bounding with employees and to retaining quality employees. Retention efforts carried out by the Company include clear and directed career development programs, leadership programs, building open and comfortable communication patterns. with employees, employee recognition, and various employee welfare programs. With the development of appropriate succession planning and supported by effective retention planning efforts, the Company will be able to supply competent human resources and have a supply of talent to fill critical position needs. in the future.